2013
DOI: 10.5455/2320-6012.ijrms20131115
|View full text |Cite
|
Sign up to set email alerts
|

Perception of fever and management practices by parents of pediatric patients

Abstract: Background: The febrile child is a common pediatric presentation in both primary care and the emergency department. An assessment of parents’ perception to recognize fever in their child, as well as management practices was the focus of this study. Methods: The study was done prospectively in which interviews were taken by researchers. One hundred and sixty four parents, whose children were less than 14 years old, had fever as one of the presenting complaints and admitted in pediatric department of Rama m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 13 publications
1
18
1
Order By: Relevance
“…Phobia of fever has been shown to affect the parents' decisions regarding seeking medical care [5]. Although parents perceive fear from fever, they have poor knowledge of fever and its consequences [6]. In 2000, a study was performed in Saudi Arabia reported that, more than two third of parents have a poor understanding of fever, high fever, untreated fever with maximum temperature, and threshold temperature which justifies the use of antipyretic medications [7].…”
Section: Introductionmentioning
confidence: 99%
“…Phobia of fever has been shown to affect the parents' decisions regarding seeking medical care [5]. Although parents perceive fear from fever, they have poor knowledge of fever and its consequences [6]. In 2000, a study was performed in Saudi Arabia reported that, more than two third of parents have a poor understanding of fever, high fever, untreated fever with maximum temperature, and threshold temperature which justifies the use of antipyretic medications [7].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast a study in Iran showed that the most common method of temperature measurement was the forehead fever strip, the reason being that many mothers being unable to read a mercury thermometer (16). However, in India (Agrawal ) 75% of the parents used the digital thermometer and the rest used the mercury thermometer (10).…”
Section: Discussionmentioning
confidence: 99%
“…In this study 58.7% used the axillary method which is lower than the rate reported in India which was 80%. (10). Similarly, Polat et al in 2012 (17) revealed that the technique of measuring the body temperature by the caregivers in Turkey was not satisfactory as caregivers stated that they were not certain about the correct site (90%) and the best type of thermometer (95%) for body temperature measurement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations